#TITLE_ALTERNATIVE# - ARIEF EFFENDHI (NIM : 12910004),
Estimating the Ocean Heat Content (OHC) can be an essential thing to predict the amount of heat content of the ocean. Calculation of OHC in Western Equatorial Pacific using the temperature in situ from Argofloat. The method to calculate the heat content on the upper layer using the two-layer model from Young et al., (2009). We analyze the heat content from surface, 150 m, 300 m, 700 m, and 2000 m depth as representative of upper, lower thermocline and deep waters. From research results on the period of 2003 – 2012, it is known that OHC of Western Equatorial Pacific is about 4.99 x 1022 J at 0 – 150 m, 5.52 x 1022 J at 0 – 300 m, 7.24 x 1022 J at 0 – 700 m, and 11.81 x 1022 J at 0 - 2000 m layer. We also know that the anomaly of OHC has a positive value (year 2008, and 2010 – 2012) and negative one (year 2003 – 2007 and 2009). On the last decade, we have a positive (negative) linear trend of OHC anomaly that indicates warming (cooling), whereas for the layer 150 m is about 2.39 MJ/m2, 300 m is 2.56 MJ/m2, 700 m is 2.66 MJ/m2, and at 2000 m is 3.57 MJ/m2. The variation of OHC is also occur spatially, where generally the warming zone is found at the center of research area 14 °N – 06 °S dan 128 °E – 157 °E (mainly at northern Head-Bird-Shaped of Papua Island). Meanwhile, the cooling zone can be found at northern Maluku Islands and southern the Equatorial area. Maps of yearly tropical OHC anomaly is also show patterns of warming commensurate with ENSO variability. OHCA and ENSO correlation results showed the presence of 1-month time lag in which the phenomenon of El Nino (La Nina) occurred 1 month earlier to the decrease (increase) in OHCA.